Non-pharmacological delirium detection and management interventions for informal caregivers of older people at home: A scoping review protocol. - Mary T Fox; Ilo-Katryn Maimets; Jeffrey I Butler; Souraya Sidani; Christina Godfrey (PLoS ONE)
Objective The objective of this proposed scoping review is to identify and map the available evidence on interventions that aim to help informal caregivers identify and/or manage delirium in an older person at home. Introduction Delirium is a neurocognitive condition characterized by acute confusion and is associated with increased risk of morbidity and mortality. Research estimates delirium to be present in 17% of community-dwellers aged 85 and older, increasing proportionally with age to 45% in those aged 90 and older. Delirium often occurs at the onset of an older person's acute illness or exacerbation of a chronic illness (sometimes while at home) and, because of its protracted nature, usually continues after a hospital stay. Even when an older person's delirium resolves during hospitalization, they remain at risk of its recurrence after discharge home. Consequently, knowing how to detect and manage delirium is critical for informal caregivers of older people at home. However, there are no reviews focused exclusively on this topic in this setting. Inclusion criteria The population of interest includes informal caregivers of a person aged 65+. Concepts of interest include delirium detection and/or management interventions. The context of interest is any setting where informal care is delivered, including the transition from hospital to home, in any geographical area. Materials and methods The review will be conducted according to the JBI guidelines for scoping reviews. A three-step search strategy will be used to locate both published and unpublished papers in MEDLINE, Embase, CINAHL, PsycINFO, Web of Science Core Collection, ProQuest Nursing & Allied Health, SCOPUS, LILACS, and SciELO, PQD&T, NDLTD, Google Scholar and Google. No language restrictions will be placed on the review. Papers will be screened for eligibility at the title, abstract, and full text level by two independent reviewers. Data will be extracted by two independent reviewers and managed in Covidence. Any disagreements in screening or data extraction will be resolved by consensus or a third reviewer. Results will be summarised in narrative and tabular formats.